2019
DOI: 10.1111/phpp.12448
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of 308‐nm excimer lamp in the treatment of scalp psoriasis: a retrospective study

Abstract: Background: Scalp psoriasis is a major therapeutic challenge due to the hindrance caused by hair. Treatment with the 308-nm excimer lamp is purported to provide many benefits over conventional phototherapy. This retrospective study evaluates the efficacy, safety, and effective dosage of 308-nm excimer light in the treatment of scalp psoriasis. Methods:We retrospectively reviewed the medical records of patients with scalp psoriasis who received treatment with 308-nm excimer light. Clinical and epidemiological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…Several studies have shown both the 308-nm excimer laser and light to be useful tools for the treatment of scalp plaques [ 26 28 ]. A 2004 study evaluated the 308 nm excimer laser for the treatment of patients who had refractory scalp psoriasis unresponsive to class I steroids and medicated shampoos [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown both the 308-nm excimer laser and light to be useful tools for the treatment of scalp plaques [ 26 28 ]. A 2004 study evaluated the 308 nm excimer laser for the treatment of patients who had refractory scalp psoriasis unresponsive to class I steroids and medicated shampoos [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with the excimer lamp was associated with a significant improvement in itch and PSSI. The most common adverse events reported were pain and erythema, but all adverse events resolved within 7 days [ 26 ]. While early results appear promising, device availability may be limited and further research is needed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies found that 308nm excimer laser was able to achieve exceptional results in the previously recalcitrant area of the scalp (5)(6)(7). A previous study using a 308-nm excimer lamp, a non-laser device, also demonstrated a similar favorable result in the treatment of scalp psoriasis with minimal and transient side effects (8). Comparing to the excimer laser, the excimer lamp has the superior advantage of being able to give uniform irradiation of 50 times wider area in a single exposure at a lower cost (9).…”
Section: Introductionmentioning
confidence: 87%
“…With 308-nm excimer light, the energy delivered to the irradiated area of skin is 5-10 times higher than that delivered with NB-UVB, and the skin lesions can also reduce the risk of skin photoaging and carcinogenesis while receiving high-energy treatment (3). Some scholars have concluded through clinical comparative studies that while there is no statistical difference in efficacy or safety between 308-nm excimer light and 308-nm excimer laser, 308-nm excimer light offers a bettermore effectiveness treatment than 308-nm excimer laser at a lower cost (4,5).…”
Section: Introductionmentioning
confidence: 99%